Morphological evaluation and determination keys of 21 citrus genotypes at seedling stage - Rahmat Budiarto; Roedhy Poerwanto; Edi Santosa; Darda Efendi (Society for Indonesian Biodiversity, 2021)
Abstract. Budiarto R, Poerwanto R, Santosa E, Efendi D. 2021. Morphological evaluation and determination keys of 21 citrus genotypes at seedling stage. Biodiversitas 22: 1570-1579. The identification of citrus varieties is generally based on flower, fruit, and mature tree characters. The detailed and comprehensive identification of seedling stage is very limited, therefore present study aimed to identify and distinguish 21 citrus genotypes based on 50 morphological characters of vegetative shoot at seedling stage. Cluster analysis using complete linkage agglomerative method showed broader dissimilarities between C. x limon and C. x microcarpa. Unfortunately, this method was limited to differentiate six genotypes within Citrus reticulata Blanco due to extremely low dissimilarities found. All citrus seedlings have similarities in the forms of habitus, gland spots, arrangement and venation of leaf. The result of PCA determined petiole wing, spine, color, hair and fragrance of leaves as five morphological markers at seedling stage. In addition, there was a positive correlation between spine and leaf pleasant. Moreover, the details of morphological dissimilarities between genotypes were described in arranged determination keys.